Analisis Return dan Kalender Anomali: Studi Komparatif Antara Saham Syariah dan Konvensional Di Indonesia - Majid, M. Shabri Abd.; Windaswari, Cut (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2015)
This research aims at empirically examiing the differences between conventional and Islamic stock returns. It also attempted to test the differences between the average return of 30-day before Eid and 30-day after Eid, and the effects of weekend, January and Ramadan on the rate of closing daily stock returns of the Jakarta Islamic Index and Index of LQ-45 in the Indonesian Stock market during the period December 1, 2009 to January 30, 2014. The method of analysis used to test the differences between the conventional and Islamic stock returns is the Independent sample t-test, while the dependent sample t-test is used to test the differences between the average return of 30-day before Eid and 30-day after Eid. Finally, to empirically examine the influence of the effects of the weekend, the January effect, and the Ramadan effect on the stock returns, the study used the Ordinary Least Square regression. The study documented that that there was no difference between the returns of Islamic and conventional stocks in Indonesia. The study also found that there was no difference between the average return of 30-day before Eid Fitri and 30-day after Eid. Finally, the study also found that there was an absence of the phenomenon of the weekend effect, January effect and the effect of Ramadan during the study period both in the Islamic and conventional stocks in Indonesia.